Схеми доставки, очищення від домішок, відмивання. Переваги, недоліки, економічна доцільність їх використання - Хоменко, Микола Дмитрович; Кухар, Володимир Миколайович (My University, 2018)
В статті розглядається якість цукрової сировини: забрудненість, подрібнення, втрати сировини і цукру при транспортуванні та очищенні цукрових буряків. Приведені кількісні величини фактичних втрат сировини в сезони переробки у 2015,2016, 2017 роках. Виявлені причини втрат. Обгрунтована необхідність удосконалювати діючі схеми, механізми та обладнання для очищення і транспортування цукрових буряків на перероблення. Рекомендовані варіати покращення ситуації шляхом удосконалення схем призаводських бурякопунктів і бурякопідготовчих відділень цукрових заводів. Розглянуто три можливих схеми з їх перевагами і недоліками. Видані рекомендації до впровадження. The article discusses the quality of sugar beets: weediness, crushing, loss of raw materials and sugar during transportation and cleaning of root crops. The quantitative values of the actual losses of raw materials in the processing seasons of 2015, 2016, 2017 are given. The causes of losses are determined. The necessity of improving existing schemes, mechanisms and equipment for cleaning and transporting sugar beets for processing is substantiated. Variants of improving the situation by improving the schemes of the beet factory and beet-preparation departments of sugar factories are recommended. Three possible schemes with their advantages and disadvantages are considered. Recommendations on their implementation were issued.
Keywords: схеми; забрудненість; втрати; очищення; рекомендації; schemes; difficulty; go; purification; recommendations